2013
DOI: 10.1016/j.pscychresns.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory timing deficits in schizophrenia

Abstract: Schizophrenia is often accompanied by disturbances in motor behavior thought to result from abnormalities in the brain’s timing mechanisms. Virtually all behavior has a motor component, and proper regulation of motor behavior is often dependent upon accurate registration of somatosensory input. This study utilizes the steady state evoked response (SSR), to quantify the accuracy of timing of the neocortical response to rapidly presented tactile somatosensory stimuli in patients with schizophrenia compared to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…For example, reduced steady-state responses have been observed with electroencephalography (EEG) at 40 Hz auditory stimulation (Krishnan et al 2009; Light et al 2006) and with magnetoencephalography (MEG) at 25 Hz somatosensory stimulation (Teale et al 2013). In the visual system, where cortical responses are tuned to 8 Hz stimuli in normal subjects (Emir et al 2008), schizophrenia patients showed reduced EEG responses in the 8–12 Hz range (Jin et al 2000; Rice et al 1989), and also at higher frequencies (Krishnan et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, reduced steady-state responses have been observed with electroencephalography (EEG) at 40 Hz auditory stimulation (Krishnan et al 2009; Light et al 2006) and with magnetoencephalography (MEG) at 25 Hz somatosensory stimulation (Teale et al 2013). In the visual system, where cortical responses are tuned to 8 Hz stimuli in normal subjects (Emir et al 2008), schizophrenia patients showed reduced EEG responses in the 8–12 Hz range (Jin et al 2000; Rice et al 1989), and also at higher frequencies (Krishnan et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the visual system, where cortical responses are tuned to 8 Hz stimuli in normal subjects (Emir et al 2008), schizophrenia patients showed reduced EEG responses in the 8–12 Hz range (Jin et al 2000; Rice et al 1989), and also at higher frequencies (Krishnan et al 2005). In addition, aberrant phase relationships and synchronization of EEG and MEG oscillations have been described in schizophrenic patients in response to auditory (Brockhaus-Dumke et al 2008; Krishnan et al 2009; Winterer et al 2000), visual (Spencer et al 2003, 2008) and somatosensory stimulation (Teale et al 2013). Furthermore, schizophrenia patients were shown to have a reduced SNR in an auditory task (Winterer et al 2000) and increased noise levels in an auditory (Winterer et al 2004) and visual task (Winterer et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine frequency-specific changes in sensory responses, we stimulated whiskers at frequencies ranging from 20 to 70 Hz. This range is important for the whisking behavior in mice (Jin et al 2004; Ritt et al 2008; Voigts et al 2008) and also encompasses frequencies at which deficits have previously been reported in patients with schizophrenia (e.g., Krishnan et al 2005; Kwon et al 1999; Teale et al 2013). Based on prior work in other schizophrenia models, we hypothesized changes in spiking and oscillatory activity during sensory stimulation relative to baseline conditions.…”
Section: Introductionmentioning
confidence: 94%
“…Using electroencephalography (EEG) or magnetoencephalography (MEG), several studies have measured neuronal activity in response to sustained visual, auditory and somatosensory stimuli in patients. Schizophrenic subjects displayed reduced amplitudes of steady-state oscillations during sustained 20–40 Hz sensory stimulation, and a decreased temporal precision of responses (Edgar et al 2013; Ikuta et al 2007; Krishnan et al 2005; Kwon et al 1999; Light et al 2006; Mulert et al 2011; Spencer et al 2008; Teale et al 2013; Tsuchimoto et al 2011). In addition to these stimulus-related deficits, an aberrant increase in oscillatory power (20–50 Hz) during baseline conditions has been observed in schizophrenic subjects (Brockhaus-Dumke et al 2008; Itil et al 1972; Kikuchi et al 2011; Spencer 2012; Venables et al 2009).…”
Section: Introductionmentioning
confidence: 99%